Proteomic analysis of Leishmania mexicana differentiation. - Nugent, P; Karsani, SA; Wait, R; Tempero, J; Smith, D (2004)
We have resolved the proteome of axenically differentiated Leishmania mexicana parasites by two-dimensional gel electrophoresis (2DE), employing optimised, robust and reproducible procedures, and visualised (by silver staining) approximately 2000 protein species in each of three developmental stages: procyclic promastigotes, metacyclic promastigotes and amastigotes. This analysis has used homogeneous populations of these parasite stages, characterised according to their morphology, protease and nuclease activity profiles and expression of stage-specific antigens. Following comparison of the whole proteome profiles between stages, 47 spots were found to be stage-specific, while a further 100 spots changed in intensity during differentiation. The majority of "unique" spots were expressed during the infective stages of parasite differentiation, metacyclic promastigotes and amastigotes. CapLC-QTOF mass spectrometry has allowed the identification of 47 protein species to date, including a number which are only detected in the amastigote stage. Proteins identified are members of eight functionally related groupings, some of which are implicated in infectivity and host-parasite interactions.